2015
DOI: 10.1017/s1368980015000233
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic inequalities in diet and body weight: evidence, causes and intervention options

Abstract: Socioeconomic inequalities in diet and body weight: evidence, causes and intervention options Diets low in fruits, vegetables and whole grains, and high in saturated fat, salt and sugar, are the major contributors to the burden of chronic diseases globally (1). Previous research, and studies in this issue of Public Health Nutrition, show that unhealthy diets are more commonly observed among socioeconomically disadvantaged groups and are key contributors to their higher rates of chronic disease (2-4). Most rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
1
20
1
Order By: Relevance
“…13 This study did not examine if environmental factors (e.g. food availability) explained or mediated socioeconomic disparities, but previous studies have found neighborhood and school-level disadvantage to be independent predictors of obesity, suggesting that both physical and social systems in which individuals operate greatly impact their health risk.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…13 This study did not examine if environmental factors (e.g. food availability) explained or mediated socioeconomic disparities, but previous studies have found neighborhood and school-level disadvantage to be independent predictors of obesity, suggesting that both physical and social systems in which individuals operate greatly impact their health risk.…”
Section: Discussionmentioning
confidence: 95%
“…10,12 These conditions may be further exacerbated by stress, social norms and low social support leading to less favorable weight-related behaviors among low SES adolescents. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The same applies for factors regarding the physical and social environment which explained part of the association between low SES and BMI. Thus, besides targeting health interventions to individuals themselves, structural interventions or policy-changes such as environmental modifications, or food procurement policies need to be considered (Turrell & Vandevijvere, 2015). Important to keep in mind are possible discrepancies between objectively measured economic or social constraints and subjective experiences of these constraints (Powell-Wiley et al, 2014).…”
Section: Theoretical and Policy Implicationsmentioning
confidence: 99%
“…Thus, in HICs there is no “one-fits-all” approach. Several authors have proposed the two perspectives are compatible [15, 16] and should not be mutually exclusive but complementary [25] because focusing only on agentic interventions does not reduce the unequal population distribution of social and economic resources which cause dietary inequalities [54]. …”
Section: Discussionmentioning
confidence: 99%